Exothermic characteristics research of chemical self-heating solution in the gas hydrate exploitation process - Zheng, Xuzhong; Wu, Dan; Zhou, Bo; Wang, Zhuangyin; Liu, Li; Yu, Junchao; Yuan, Qing; Jiang, Song; Zhao, Jiamin; Wang, Yue (Frontiers in Energy Research, 2022)
Thermal stimulation methods of hydrate exploitation with chemical self-heating solution began to be investigated in the recent years. However, the exothermic characteristics of chemical self-heating solution during the gas hydrate exploitation process was not investigated systematically now. In this work, the effects of reagent concentration, acid variety, acid concentration on the exothermic characteristics were investigated by a self-designed high pressure autoclave with a 11.75 L volume, whose diameter and length is 100 and 1,500 mm, respectively. The experimental results showed that the temperature of hydrate reservoir will change in a wide range (from 100°C to −3°C) during the injection process of self-heating solution which was a large challenge to control the rate of heat release. During the self-heating solution injection, the temperature decreased quickly because of the strong endothermic reaction of hydrate dissociation promoted by the salt effect of self-heating solution, and then the temperature increased quickly because of exothermic reaction of self-heating solution. The exothermic rate of self-heating solution increased with the increase of reagent concentration, the acid concentration and the acidity. In all of the experiments, the temperatures near the inlet entrance were much higher than that in the deeper area, which illustrated that the effective heating area is the areas near the entrance. In the end, the different injection mode of mixed injection and sectional injection was also investigated, and it was found that the temperature peak in the near area with mixed injection mode is higher than that with sectional injection mode, however, the exothermic performance with sectional injection mode is better than that with mixed injection in the area far away from the inlet entrance. The exothermic characteristics studies of self-heating solution in this work can lay the necessary foundation of the further studies of self-heating solution in the exploitation of natural gas hydrate.